The politics of laughter at the 2nd Sol Rindo, a clowning festival at Balneário Camboriú: an interview with Bruna Pierami and Monique Neves from Cia As Mareadas - Miranda, Maria Brígida de; Alvarez, Beatriz Costa; Lopes, Lorena Maria (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
The Argentine theatre researcher Lorena Maria Lopes in the context of her intercultural PhD research linked to the MOVE LA America Program (CAPES, Brazil) conducted this interview. It is part of a broader set of investigations carried out with Brazilian women working in clowning and performing arts. The first empirical field of the research was the 2nd Sol Rindo – Festival de Palhaçaria de Balneário Camboriú, held from April 5 to 8, 2025, organized by Cia As Mareadas in partnership with Beatriz Costa Alvarez and Cia Ler e Viver. This clowning festival received funding from the National Aldir Blanc Policy (PNAB), in addition to support from private institutions. The interview selected for this issue of Revista Ephemera, whose thematic dossier is “The collective body of laughter,” was conducted with the festival’s producers, Monique Neves and Bruna Pierami, who are actresses, clowns, and feminist activists. The article contextualizes the trajectory of the festival and the growth of clowning performed by women in Brazil, highlighting networks such as the Rede Catarina de Palhaças and academic and editorial productions focused on the theme. The interview was conducted in an intimate setting, guided by a feminist ethics of care, and was fully transcribed. Lorena Maria Lopes’s research focuses on lesbian visibility, understood as a field of political militancy inscribed in the theatrical scene of Balneário Camboriú, where the work of the collective of married lesbian women known as As Mareadas stands out.